Menggugat Legitimasi Budaya: Kritik Etika Sosial Kristen Terhadap Kekerasan Seksual dalam Adat Sifon - Yesika Maubanu; Irene Ludji; Mariska Lauterboom (Institut Agama Kristen Negeri Palangka Raya, 2026)
The Sifon customary circumcision practice is a traditional male circumcision ritual that contains elements of sexual violence against women. This study examines women’s experiences within this tradition through the lens of Christian social ethics, employing a qualitative ethnographic approach. The findings reveal that the Sifon custom represents a systematic and institutionalized form of violence, in which women’s bodies are objectified as instruments in male healing rituals. This tradition normalizes sexual violence and reinforces the marginalization of women within the social structure of the community. From the perspective of Christian Social Ethics, this practice violates human dignity, social justice, and love for others. The sexual exploitation legitimized through cultural symbols reflects structural injustice that requires critical theological and social interpretation. The implications of this study underscore the importance of an ethical approach that prioritizes the rights of victims, fosters gender-sensitive cultural awareness, and supports social reconstruction that restores women’s dignity. Therefore, the Sifon customary practice is not merely a cultural heritage but an institutionalized form of sexual violence. Christian Social Ethics provides a moral foundation to deconstruct oppressive cultural legitimations and to promote social transformation that is just, equal, and respectful of women as dignified creations of God.